Making it : the artist's survival guide - JAŠA, 1978-; Charney, Noah (Rowman & Littlefield, 2021)
"Here's a book for aspiring artists written by a successful artist. Combining the author's own story with answers to the tough questions rising artists inevitably have, this book is not only about the creative process but also about navigating the turbulent waters of the social, professional, critical, and museum world artists inhabit"--